Touching the unconscious in the unconscious – hypnotic communication with unconscious patients - Hansen, Ernil (Frontiers in Psychology, 2024)
If hypnosis means contact to the unconscious to modulate psychological and physiological functions by means of suggestions, and if this is facilitated by attenuation of the critical mind, then the question arises as to whether suggestions also have an effect when waking consciousness is otherwise eliminated, namely by coma or anesthesia. A prerequisite would be perception, which actually is evidenced by reports of patients after traumatic brain injury, artificial coma, resuscitation or general anesthesia. Moreover, posttraumatic stress disorder (PTSD) frequently observed after these medical situations is hardly explainable without some sort of awareness under such conditions. Even advanced neurophysiological diagnostic cannot yet rule out consciousness or sensory processing.Especially reference to perception during unconsciousness is given by the results of a recent multicenter study on the effects of hypnotic communication with patients under controlled adequate deep general anesthesia. The observed reductions in incidence and severity of postoperative pain, opioid use, nausea and vomiting cannot be explained by the reaction of a few but only by a considerable proportion of patients. This leads to a strong plea for a more careful treatment of unconscious patients in the emergency room, operating theater or intensive care unit, for the abandonment of the restriction of therapeutic communication to awake patients, and for new aspects of communication and hypnosis research. Obviously, loss of consciousness does not protect against psychological injury, and continuation of communication is needed. But how and what to talk to unconscious patients? Generally addressing the unconscious mind with suggestions that generally exert their effects unconsciously, hypnotic communication appears to be the adequate language.Especially addressing meaningful topics, as derived from the basic psychological needs and known stressors, appears essential. With respect to negative effects by negative or missing communication or to the proposed protective and supporting effects of therapeutic communication with patients clinically rated as unconscious, the role of consciousness is secondary. For the effects of perceived signals and suggestions it does not matter whether consciousness is absent, or partial, or unrecognized present.